Enterprice competitiveness analysis - Tsyntsovska, Т. O. (NAU, 2021)
Competitors took a part in the interior of the country and in the name of the world, and the scientific and technological development of the domains of the subspecies of the living, the uniqueness of which is to be adapted to the novelties of mind and mission. Competition has always been important in domestic and external markets. Competitiveness is the most important indicator of the state of production. Competitiveness determines position in the market space, development perspective, ability to achieve strategic objectives. Accurate analysis of own benefits will help to improve management and reach the peak competitiveness. Competitivity - this is a complex comparative features, which shows the transformation of general mark of production ability.
Keywords: competitiveness; management; information processing; strategic industry group maps; market space is; stability in market space